Diagnostic and prognostic biomarkers in immune checkpoint inhibitor-related encephalitis: a retrospective cohort studyResearch in context - Antonio Farina; Macarena Villagrán-García; Anthony Fourier; Anne-Laurie Pinto; Fatima Chorfa; Noémie Timestit; Tifanie Alberto; Jérôme Aupy; Marie Benaiteau; Cristina Birzu; Lucia Campetella; François Cotton; et al. (Elsevier, 2024)
Summary: Background: Immune checkpoint inhibitor-related encephalitis (ICI-encephalitis) is not well characterised and diagnostic and prognostic biomarkers are lacking. We aimed to comprehensively characterise ICI-encephalitis and identify diagnostic biomarkers and outcome predictors. Methods: This retrospective observational study included all patients with ICI-encephalitis studied in the French Reference Centre on Paraneoplastic Neurological Syndromes (PNS) and Autoimmune Encephalitis (2015-2023). ICI encephalitis was considered definite in case of inflammatory findings at paraclinical tests and/or well-characterised neural antibodies. Predictors of immune-related adverse event (irAE) treatment response, defined as a Common Terminology Criteria for Adverse Events v5.0 grade < 3 at any time after therapeutic intervention, were assessed by logistic regression analysis, and predictors of mortality by Cox regression analysis. Neurofilament light chain (NfL) was measured by enzyme-linked immunosorbent assay. Findings: Sixty-seven patients with definite encephalitis were identified (median age, 69 years; 66% male). A focal syndrome was observed in 43/67 patients (64%; limbic encephalitis, cerebellar ataxia, and/or brainstem encephalitis), while 24/67 (36%) had meningoencephalitis, a non-focal syndrome with altered mental status (22/24 patients, 92%) and pleocytosis (24/24 patients, 100%). Patients with focal encephalitis more frequently had abnormal brain MRI (26/42, 62% versus 8/24, 33%, p = 0.025), PNS-related antibodies (36/43, 84% versus 1/24, 4%, p < 0.001), and neuroendocrine cancers (22/43, 51% versus 1/24, 4%; p < 0.001) than patients with meningoencephalitis. Focal encephalitis patients had a lower rate of irAE treatment response (7/39, 18%) and higher mortality (27/43, 63%) compared to meningoencephalitis patients (12/22, 77% and 5/24, 21%, respectively, p < 0.001 each). PNS-related antibodies were associated with less irAE treatment response, independently of age, sex, and baseline severity (adjusted OR 0.05; 95%CI [0.01; 0.19]; p < 0.001) as well as higher mortality, independently of age and cancer type (adjusted HR 5.07; 95% CI [2.12; 12.12]; p < 0.001). Serum NfL discriminated patients with definite ICI-encephalitis (n = 27) from cancer-matched controls (n = 16; optimal cut-off >273.5 pg/mL, sensitivity 81%, specificity 88%, AUC 0.87, 95% CI [0.76; 0.98]) and irAE treatment responders (n = 10) from non-responders (n = 17, optimal cut-off >645 pg/mL, sensitivity 90%, specificity 65%; AUC 0.75, 95% CI [0.55; 0.94]). Interpretation: ICI-encephalitis corresponds to a set of clinically-recognisable syndromes. Patients with focal encephalitis, PNS-related antibodies, and/or higher serum NfL have low irAE treatment response rates. Research is needed on the underlying immunopathogenesis to foster therapeutic innovations. Funding: Agence Nationale de la Recherche.